Síndrome Urémico Hemolítico y yogur: entre la creencia popular y la evidencia científica - Vinderola, Celso Gabriel (2020)
Some health professionals discourage yogurt because of the risk of Hemolytic Uremic Syndrome (HUS), a serious disease caused by strains of Shiga toxin-producing E. coli (STEC). These bacteria can pass from the intestine of cattle to meat or milk under inadequate working conditions in slaughterhouses or milking plants. Undercooked hamburgers the main is vector of disease and unpasteurized raw milk or dairy products made with it, are another risk factors. In the dairy industry, yoghurt is made from milk that undergoes a double heat treatment. There are no reports of the presence of STEC in industrial yogurts in the modern bibliography, and reviews and meta-analysis do not point to yogurt as a risk factor for STEC, but rather unpasteurized milk. In this context, and given the scientific evidence currently available regarding STEC, HUS and yogurt, it would seem that we are in the presence of a spurious correlation, the association between two facts that have no causal relationship between them, rather than a scientific fact for which one (yogurt) may be responsible for the other (HUS).